2024
DOI: 10.21511/ppm.22(1).2024.12
|View full text |Cite
|
Sign up to set email alerts
|

Does managerial ability matter in corporate sustainability-related dynamics? An empirical investigation

Oleh Pasko,
Li Zhang,
Edward Markwei Martey
et al.

Abstract: This study aims to assess the intricate interplays between managerial ability, corporate social responsibility (CSR), and firm value, focusing on 3,498 company-year observations sourced from the RANKINS CSR RATINGS and China Stock Market & Accounting Research (CSMAR) databases representing China’s Shanghai and Shenzhen A-share listed companies from 2009 to 2018. Employing a rigorous sample selection process and utilizing data from reliable databases, the research employs a comprehensive methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In the context of the CSR concept, the crucial moment came when Carroll (1979) proposed a definition of CSR issuing from four pillars: economic, ethical, legal, and philanthropic. Hoffman and Bazerman (2007) concluded that the reason for introducing CSR rules in companies is not just business-led, but that formal acceptance and implementation of CSR by companies may also be linked to the changing of personal values (Ostapenko et al, 2022;Thao et al, 2023;Pasko et al, 2024). The triple bottom line (TBL) concept asserts that for a company to ensure its sustainability, it must simultaneously meet social expectations and minimize adverse impacts on society across the three pillars of social, environmental, and economic domains (Tate & Bals, 2018; Colbert & Kurucz, 2007) while maintaining the financial well-being of the organization (Colbert & Kurucz, 2007).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…In the context of the CSR concept, the crucial moment came when Carroll (1979) proposed a definition of CSR issuing from four pillars: economic, ethical, legal, and philanthropic. Hoffman and Bazerman (2007) concluded that the reason for introducing CSR rules in companies is not just business-led, but that formal acceptance and implementation of CSR by companies may also be linked to the changing of personal values (Ostapenko et al, 2022;Thao et al, 2023;Pasko et al, 2024). The triple bottom line (TBL) concept asserts that for a company to ensure its sustainability, it must simultaneously meet social expectations and minimize adverse impacts on society across the three pillars of social, environmental, and economic domains (Tate & Bals, 2018; Colbert & Kurucz, 2007) while maintaining the financial well-being of the organization (Colbert & Kurucz, 2007).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%